Targeting prostate cancer stem cells for cancer therapy - Wang, Guocan (2012)
Prostate cancer (PCa) is the most common malignant neoplasm in men and the second most frequent cause of cancer death for males in the United States. Recently, emerging evidence suggests that prostate cancer stem cells (CSCs) may play a critical role in the development and progression of PCa. Therefore, targeting prostate CSCs for the prevention of tumor progression and treatment of PCa could become a novel strategy for better treatment of patients diagnosed with PCa. In this review article, we will summarize the most recent advances in the prostate CSCs field, with particular emphasis on targeting prostate CSCs to treat prostate cancer.